Genetic evidence for a fall-spawning group of Gulf sturgeon (Acipenser oxyrinchus desotoi) in the Apalachicola River, Florida, USA - Jacob O. Zona; Brian R. Kreiser; Adam J. Kaeser; Adam G. Fox; Mark J. D’Ercole (PLoS ONE, 2025)
The Gulf sturgeon ( Acipenser oxyrinchus desotoi ) is a large, long-lived, anadromous fish inhabiting the northern Gulf of Mexico. This charismatic fish was hunted to near extinction in the early 1900s. In 1991 the subspecies was listed as threatened under the Endangered Species Act. Recovery continues to be challenged by threats such as habitat destruction, fisheries bycatch, and climate change. There are seven known natal rivers. Historically, each river was thought to contain a single, spring-spawning group. Recent studies have discovered several rivers (Suwannee, Choctawhatchee) contain a second, fall-spawning group. This study utilizes genetic techniques to investigate the proposed existence of a fall-spawning group in the Apalachicola River, Florida. Juvenile Gulf sturgeon were sampled between May and July, from 2013 to 2022. Four adults were also captured on the spawning grounds during October of 2022. Samples were genotyped for thirteen microsatellite loci to assess genetic population structure within the Apalachicola River. Analyses detected two distinct genetic groups (F ST = 0.085). Dates of capture, length frequency distributions of juveniles, and genetic assignment of spawning adults allowed us to characterize these as separate spring- and fall-spawning groups. While approximately 90% of juveniles collected were assigned to the spring, only slight differences in genetic diversity were detected between groups. The temperature window for spawning was found to be three weeks shorter on average in the fall than the spring, highlighting the need for additional research into differing environmental or anthropogenic influences on these populations. The discovery of a fall-spawning group of Gulf sturgeon in the Apalachicola River improves our understanding of the representation, redundancy, and resiliency of the species and provides critical information for improved management of this river system.